PENGUATAN IDEOLOGI PANCASILA DALAM KONTEKS PERTAHANAN DAN KEAMANAN NASIONAL - Hasbullah Hasbullah; Andi Agustang; Idham Irwansyah Idrus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
Pancasila as the ideology of the Indonesian State has such an important role in building national resilience, including in the context of defense and security. Many foreign ideologies have entered and many propaganda have sprung up in society, so there is a possibility that disturbances will occur in various sectors such as social, cultural, economic, political and even in the national defense and security sector. Therefore, it is necessary to strengthen Pancasila Ideology in the Context of National Defense and Security. This study uses a qualitative approach by conducting literature studies on various sources that are relevant to the research theme. The researcher conducted a text analysis and concluded the findings resulting from the analyzed literature. The results of this study indicate that the strengthening of Pancasila ideology in the context of national defense and security has a very important role in maintaining national defense and security. The values contained in Pancasila become a strong ideological foundation and can strengthen a sense of nationalism and love for the motherland.